2013
DOI: 10.1371/journal.pone.0084381
|View full text |Cite
|
Sign up to set email alerts
|

Straight Line Foraging in Yellow-Eyed Penguins: New Insights into Cascading Fisheries Effects and Orientation Capabilities of Marine Predators

Abstract: Free-ranging marine predators rarely search for prey along straight lines because dynamic ocean processes usually require complex search strategies. If linear movement patterns occur they are usually associated with travelling events or migratory behaviour. However, recent fine scale tracking of flying seabirds has revealed straight-line movements while birds followed fishing vessels. Unlike flying seabirds, penguins are not known to target and follow fishing vessels. Yet yellow-eyed penguins from New Zealand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 36 publications
(68 reference statements)
0
49
0
Order By: Relevance
“…Preston et al (2008) observed that the diving shape profiles and foraging locations of penguins corresponded with the locations and physical features (e.g., depth, angle) of the shipping channel and suggested penguins may be using shipping channels to reduce the escape field of prey. However, if penguins are using shipping channels to improve capture success rate then we would expect their foraging trajectories to be linear, similar to the tracks of yellow-eyed penguins (Megadyptes antipodes) in the Otago Peninsula, that travel in straight lines for several kilometers following demersal fish trawl furrows on the seafloor (Mattern et al, 2013), or zigzagged, reflecting the continued use of the shipping channel. Furthermore, if exploiting shipping channels is a means to improve foraging efficiency, we would expect the foraging ranges of a greater proportion of sampled penguins to overlap with the shipping channel.…”
Section: Environmental Differences Between the Home-range And Core-ramentioning
confidence: 94%
“…Preston et al (2008) observed that the diving shape profiles and foraging locations of penguins corresponded with the locations and physical features (e.g., depth, angle) of the shipping channel and suggested penguins may be using shipping channels to reduce the escape field of prey. However, if penguins are using shipping channels to improve capture success rate then we would expect their foraging trajectories to be linear, similar to the tracks of yellow-eyed penguins (Megadyptes antipodes) in the Otago Peninsula, that travel in straight lines for several kilometers following demersal fish trawl furrows on the seafloor (Mattern et al, 2013), or zigzagged, reflecting the continued use of the shipping channel. Furthermore, if exploiting shipping channels is a means to improve foraging efficiency, we would expect the foraging ranges of a greater proportion of sampled penguins to overlap with the shipping channel.…”
Section: Environmental Differences Between the Home-range And Core-ramentioning
confidence: 94%
“…YEP is a species of significant cultural and economic value for New Zealand (Seddon, Ellenberg & van Heezik, 2013). Particularly the tourism industry of the Otago Peninsula benefits from the presence of the birds with YEPs contributing more than NZ$100 mio annually to the local economy.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other penguins, the YEP's distributional range is fairly limited. About 60% of the species' population is thought to inhabit the sub-Antarctic Auckland and Campbell Islands, while the remaining ∼40% breed along the south-eastern coastline of New Zealand's South Island (Seddon, Ellenberg & van Heezik, 2013). Genetic analyses revealed that there is virtually no gene flow between the sub-Antarctic and mainland YEP populations (Boessenkool et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that this strategy might come at the expense of reduced 84 behavioural flexibility, with subsequent vulnerability to changes in the marine environment (Mattern 85 et al 2007). In particular, degradation of seafloor ecosystems in the wake of commercial bottom 86 fisheries are suspected to influence yellow-eyed penguin foraging success and population 87 developments (Browne et al 2011; Mattern et al 2013). While the species' at-sea movement and 88 diving behaviour has been subject to a number of studies in the past decades (Moore et al 1995;89 Mattern et al 200789 Mattern et al , 2013), information about their benthic habitat is scarce.…”
mentioning
confidence: 99%
“…This study was carried out at the Boulder Beach 105 complex, Otago Peninsula, South Island, New Zealand (45.90°S, 170.56°E). Penguins from this site 106 have been subject to foraging studies in the past decade that have suggested substantial impact of 107 bottom trawling activities on the yellow-eyed penguins' at-sea movements (Mattern et al 2013). 108…”
mentioning
confidence: 99%